Implementasi Tugas Penggembalaan Berdasarkan Mazmur 23:1-4 Bagi Pemimpin Gereja Masa Kini - Marco Menang Iman Padang; Rut Kristina Hutabarat; Grecetinovitria Merliana Butar Butar (Journal New Light, 2024)
In recent years, the church has faced great challenges in fulfilling its role as a shepherd who leads, protects, and nurtures the congregation. Church leadership that lacks this role has led to instability and lack of clear direction among the congregation. This paper aims to highlight the importance of implementing Psalm 23:1-4 in today's church. Using the text analysis method, this study delves deeply into the meaning and implications of these verses and applies them to church leadership today. Church leaders are able to understand their responsibilities as pastors and to apply the principles contained in Psalm 23:1-4 in their ministry to the congregation.